The expression and relaxant effect of bitter taste receptors in human bronchi - Grassin-Delyle, Stanislas (BioMed Central, 2013)
BACKGROUND: Bitter-taste receptors (TAS2Rs) have recently been involved in the relaxation of mouse and guinea pig airways, and increased expression of TAS2Rs was shown in blood leucocytes from asthmatic children. We sought to identify and characterize the TAS2Rs expressed in isolated human bronchi and the subtypes involved in relaxation. METHODS: Human bronchi were isolated from resected lungs and TAS2R transcripts were assessed with RT-qPCR. Relaxation to TAS2R agonists was tested in organ bath in the presence or absence of pharmacological modulators of the signalling pathways involved in bronchial relaxation. RESULTS: We detected the expression of TAS2R transcripts in human bronchi. The non-selective agonists chloroquine, quinine, caffeine, strychnine and diphenidol produced a bronchial relaxation as effective and potent as theophylline but much less potent than formoterol and isoproterenol. Denatonium, saccharin and colchicine did not produce relaxation. Receptor expression analysis together with the use of selective agonists suggest a predominant role for TAS2R5, 10 and 14 in bitter taste agonist-induced relaxation. The mechanism of relaxation was independent of the signalling pathways modulated by conventional bronchodilators and may be partly explained by the inhibition of phosphatidylinositol-3-kinases. CONCLUSIONS: The TAS2Rs may constitute a new therapeutic target in chronic obstructive lung diseases such as asthma.